Pragmatic Study of High School Teacher Directive Speech Acts in Classroom Teaching and Learning Activities - Abd. Rahman Rahim (Institute of Computer Science (IOCS), 2022)
Teachers engage in speech acts that have certain qualities in order to develop effective communication with students by utilizing a variety of approaches and strategies of speaking, while also taking into consideration the context of formal or casual situations. This research was conducted at SMA Bonerate Makassar with the intention of elucidating the manner in which instructors use directive speech acts in the context of instructional and educational activities. This is an example of a qualitative research approach that utilizes the descriptive method. The findings indicated that the teacher's directive speech act is a structured and planned communication act between the teacher and students in both formal and informal settings, that the teacher's directive speech act determines the success or failure of the learning process in the classroom, and that the teacher's directive speech act will reflect the teacher's communication competence in carrying out their duty as an educator